2015
DOI: 10.1007/s40615-015-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparity in Utilization of General Dental Care Services Among US Adults: Medical Expenditure Panel Survey 2012

Abstract: Objective The objective of this study was to examine racial/ ethnic disparity and associated factors in general dental care utilization among US adults. Methods Data were adults 18-85 years old (N = 27,394) from the 2012 Medical Expenditure Panel Survey (MEPS). The outcome was the receipt of general dental care, measured by (1) whether the individual has ever had a general dental visit and (2) the number of general dental visits the individual has had during the past year. Race/ethnicity was the primary intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
4
12
0
Order By: Relevance
“…Similar to several studies using cross-sectional data, we found that Blacks, Hispanics, and other racial/ethnic minorities reported a lower rate of service utilization than Whites (Christian et al, 2013; Shelley et al, 2011; Wu et al, 2013; Zhang, 2016). However, the current study went beyond prior research by confirming that racial/ethnic disparities were substantial and persistent as people became older regardless of birthplace while adjusting for a wide range of covariates.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to several studies using cross-sectional data, we found that Blacks, Hispanics, and other racial/ethnic minorities reported a lower rate of service utilization than Whites (Christian et al, 2013; Shelley et al, 2011; Wu et al, 2013; Zhang, 2016). However, the current study went beyond prior research by confirming that racial/ethnic disparities were substantial and persistent as people became older regardless of birthplace while adjusting for a wide range of covariates.…”
Section: Discussionsupporting
confidence: 87%
“…Regular dental checkups can prevent oral diseases, maintain good oral health (Griffin, Jones, Brunson, Griffin, & Bailey, 2012), and promote cognitive functioning in late life (Han, Wu, & Burr, 2019). However, regularly utilizing dental services is often a challenge for many Americans, especially for older adults, racial/ethnic minorities, and immigrant populations (Wilson, Wang, Borrell, Bae, & Stimpson, 2018; Zhang, 2016). This is mainly due to barriers such as lack of dental insurance coverage, access to quality dental care, and awareness of the importance of oral health (Wu, Liang, Luo, & Furter, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we failed to find evidence that reports of delaying dental care differed by race and ethnicity. Racial and ethnic inequities in use of dental care prepandemic are well documented, with non-White adults being less likely to visit a dentist (Zhang 2016), yet our analyses suggest that non-White adults were not disproportionally affected as it relates to delayed dental care. Because the COVID-19 pandemic has disproportionally impacted Black and Hispanic individuals (CDC 2020b) and because Black and Hispanic adults are more likely to have unmet dental needs than White adults (Bhoopathi et al 2020), it is important to monitor and confirm access to dental care among non-White populations during the pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, a primary aim of this analysis was to assess the influence of additional factors on dental care utilization, after accounting for these financial barriers. Based on prior research, we hypothesized that individuals with lower incomes, those with lower education levels, and those living in rural areas would be less likely to see a dentist [ 6 , 21 – 23 ]. Based on common health promotion theories and supporting research, we also hypothesized that individuals with higher levels of motivation and self-efficacy for seeing a dentist would be more likely to do so [ 24 29 ].…”
Section: Introductionmentioning
confidence: 99%